(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2018)
Drying is one of the most popular traditional food preservation processes today. It consists of removing free water using hot air as a drying medium. Drying involves complex and simultaneous mechanisms of heat, mass, and momentum transfer. Temperature is one of the main process variables. If it is not adequate, it affects product quality by altering flavor, color, odor, and other attributes, and diminishes nutritional content.